Labor markets and multinational enterprises in Puerto Rico : foreign direct investment influences and sustainable growth /: foreign direct investment influences and sustainable growth. (2015) - Juma'h, Ahmad H; Morales Rodríguez, Doris J; Lloréns-Rivera, Antonio, 1964-
No abstract available